POLITISASI KONSTITUSI PIUTANG NEGARA DI INDONESIA - Pandoman, Agus (Wacana Hukum, 2018)
AbstractOne example of the problems in the state's claim is BLBI extended by Bank Indonesia to the national banking system, which has become the state's claim, but not resolved through PUPN, but further right to claim the government handed over to IBRA established by Presidential Decree No. 27 of 1998 . Since handed over to the government the right to collect BI, BI ended authority to withdraw BLBI of the receiving bank, resolved through non-litigation and mechanisms and the solution was not to use repressive laws. Receivables BLBI state is a case of default the unusually large number (extraordinary default), but penyelesaianya by IBRA implemented with the exclusion of the legal principles of the settlement of accounts receivable against the debtor country BLBI receiver, so in this case the journey is also a cost for settling disputes outstanding a big. This paper would like to see how the practice of politicizing the constitution that happens particularly with respect to issues of State receivables.AbstrakSalah satu contoh kasus persoalan dalam piutang negara adalah kasus BLBI yang disalurkan oleh Bank Indonesia kepada perbankan nasional, yang sudah menjadi piutang negara, namun tidak diselesaikan melalui PUPN, akan tetapi selanjutnya hak tagih tersebut diserahkan pemerintah kepada BPPN yang dibentuk berdasarkan Keppres Nomor 27 Tahun 1998. Sejak diserahkan hak tagih BI kepada pemerintah, berakhirlah wewenang BI untuk menarik kembali BLBI dari bank penerima, diselesaikan melalui jalur dan mekanisme non-litigasidan penyelesaiannya pun tidak menggunakan hukum represif. Piutang negara BLBI adalah kasus gagal bayar yang jumlahnya luar biasa besar (extraordinary default), akan tetapi penyelesaianya oleh BPPN dilaksanakan dengan mengesampingkan prinsip-prinsip hukum penyelesaian piutang negara terhadap debitur penerima BLBI, sehingga dalam perjalanannya kasus ini juga menelan biaya penyelesaian perkara yang luar biasa besar. Tulisan ini ingin melihat bagaimana praktek politisasi konstitusi itu terjadi khususnya terkait dengan masalah piutang Negara.